Spleen EBV-positive inflammatory follicular dendritic cell sarcoma: a case report and literature review - Yi Xiao; Lanlan Li; Xiumei Zhan; Juner Xu; Yewu Chen; Qiuchan Zhao; Yinghao Fu; Xian Luo; Huadi Chen; Hao Xu (Frontiers in Oncology)
Epstein–Barr virus-positive inflammatory follicular dendritic cell sarcoma (EBV+ IFDCS) is a rare tumor that typically arises in the liver or spleen and is characterized by spindle-shaped cells within a dense lymphoplasmacytic background. We report a case of a 64-year-old woman with an incidental splenic mass found during routine imaging. MRI showed a 4.8 cm lesion with progressive enhancement. The patient underwent laparoscopic partial splenectomy. Histopathological examination revealed features consistent with EBV+ IFDCS, including positivity for CD21, CD23, CD35, SMA, EMA, and EBER. EBV+ IFDCS often presents with nonspecific symptoms and imaging findings, making diagnosis challenging. Definitive diagnosis relies on histology, immunohistochemistry, and confirmation of EBV infection. Most cases follow an indolent clinical course and have a favorable prognosis after complete surgical resection, though rare aggressive cases have been reported. Understanding its clinicopathological and molecular features is essential for accurate diagnosis and management.